6 SCUTI STAR GX PEGASI: ADDITIONAL ANALYSIS - Repin, S. V.; Michel, E.; Auvergne, M.; Baglin, A.; Goupil, M. J.; Gurin, L. S.; Samoilova, Yu. O. (Одеські астрономічні публікації, 2017)
Three criteria of the periodicity are discussed in the paper and their properties are investigated. These criteria are applied to investigate the periodicity properties of a variable star GX Pegasi. A number of periodic components are extracted.